Linia falista i totalność. Efektowność i efektywność poezji Kamili Janiak - Poręba, Karol (Śląskie Studia Polonistyczne, 2019)
The aim of this article is to discuss poetic works by Kamila Janiak using categories of showiness (a formal surplus) and efficiency (understood as critical or per-formative potential). The author of the article comments upon the early reception of Janiak’s poems to point that first reviewers oftentimes intuitively indicated the totality of Janiak’s poetic gestures, and then he traces the poetess’s strategy back to Camp aesthetics.